Effects of fatigue on rugby place kicking technique and performance - Bull, H.; Murphy, C.; Gilham, J.; Atack, A. C. (ISBS Proceedings Archive (Michigan), 2022)
The aim of this study was to identify differences in place kicking performance and technique following a rugby-specific fatigue protocol. Three skilled place kickers performed four blocks of the protocol, between which they took three place kicks from a challenging pitch location. The success of the kicks, measures of physical exertion and lower body and torso kinematic variables were measured. Kicking success dropped following blocks 2 and 4 of the protocol, all missed kicks were wide of the goalposts. Individual differences were apparent. After block 2 the kickers demonstrated greater upper body motion, potentially a strategy to obtain fast foot velocity but at a detriment to accuracy. After block 4, collapse of the stance leg was observed which may have impacted the kickers` stability. Further research with more participants and a specific focus on muscular fatigue is required.